Designing Reading Texts and Tasks for Differentiated Literacy Learning - Ella Wulandari; Sukarno Sukarno (The Journal of English Literacy Education: The Teaching and Learning of English as A Foreign Language, 2024)
This paper presents the findings of the research stage of the research and development project in developing levelled reading tasks for secondary school learning of English. The participants included 305 students and 9 English teachers in 5 schools in Yogyakarta. A needs survey was administered to explore students and teachers’ target and learning needs for reading instructions. A focus-group discussion with the teachers was held to provide confirmation to the results of needs analysis. The findings indicated that both student and teacher participants viewed text comprehension as the foundational skill that improves literacy and hence reading texts (input) must be comprehensible for students to benefit from the activities of reading (procedure). Glossed texts between 250 – 350 words length are most-opted and discussing the text is the most preferred literacy engagement. The students also perceived themselves as an active reader who seeks for meaning clarification either with peers or independently. This view aligned with the teachers’ inclination for promoting higher level reading processing to support literacy. Implications for equipping teachers with text and task adaptation skills to promote higher-level literacy are discussed.